Knowledge and skills of nurse educators regarding curriculum development in nursing education institutions in Gauteng Province, South Africa - Bhana-Pema, Varshika (University of Pretoria, 2023)
Dissertation (MNur (Nursing Science))--University of Pretoria, 2023.